Gate‐Defined Quantum Confinement in CVD 2D WS2 (Adv. Mater. 25/2022). Issue 25 (23rd June 2022) - Lau, Chit Siong; Chee, Jing Yee; Cao, Liemao; Ooi, Zi‐En; Tong, Shi Wun; Bosman, Michel; Bussolotti, Fabio; Deng, Tianqi; Wu, Gang; Yang, Shuo‐Wang; Wang, Tong; Teo, Siew Lang; et al.
Abstract : Quantum Dots In article 2103907, Kuan Eng Johnson Goh and co‐workers report electrostatically defined quantum dots in bilayer WS2 grown by chemical vapor deposition and capped by HfO2 dielectric using atomic layer deposition. This marks a key milestone in scalable approaches toward 2D‐semiconductor‐based quantum devices, which had hitherto only been demonstrated with micrometer‐sized exfoliated flakes.